‘A Foreign Plant’: Citizen-Initiated Referendums and Democratic Conceptualisations in the Netherlands, 1966-1999 - Lammerts van Bueren, Jelle (BMGN - Low Countries Historical Review, 2026)
From the mid-1960s onwards, the distanced model of postwar Dutch democracy, which used to be characterised by well-established political parties, top-down forms of citizen participation, and a powerful bureaucratic class, became heavily scrutinised. This article argues that in the ensuing atmosphere of competing democratic conceptualisations, the binding citizen-initiated referendum became one of the central battlegrounds in the debate over the correct practices of democracy. In this battle, that not only took place along, but also across party lines, the theoretical notion of parliamentary primacy was nonetheless deemed inviolable. Consequently, the referendum remained merely one of the many proposals for democratic renovation to close the gap between politicians and citizens. This allowed its opponents to instead choose other, more parliament-oriented reforms.